Image Rejuvenation In The Digital Era: PT Bank Rakyat Indonesia (Persero) Tbk's Image Build And Develop Strategy In Winning Gen Z Loyalty - Arizal Fendy Pradana; Herdhani Nafisa; Cornellyo Andrea P; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
This research is driven by the phenomenon of macroeconomic volatility in early 2026, triggered by the transition to the INDONIA interest rate as the sole benchmark replacing JIBOR. This dynamic created significant reputation risks and information asymmetry for the national banking sector, particularly for PT Bank Rakyat Indonesia (Persero) Tbk. This conceptual study aims to formulate a reconstruction of an adaptive financial communication and reputation management model to mitigate these risks while winning the loyalty of the new generation market. Using a qualitative descriptive approach through conceptual analysis based on Signaling Theory and Information Subsidies, the results indicate that BRI’s success lies in a strategic balance between building a new "Modern-Agile" image and developing existing "heritage trust". The implementation of the "3T" communication model—Transparent, Technical, and Timely—in corporate news releases proved effective in reducing market speculation. Quantitative data transparency and the speed of information distribution were found to correlate linearly with the stability of investor confidence and digital customer satisfaction. Ultimately, BRI successfully rejuvenated its brand to attract Gen Z without alienating its traditional micro-customer base. The research concludes that transforming the Public Relations function into an "accountable data center" is an urgent necessity for systemic banks to maintain reputation resilience amidst monetary uncertainty.